First Name Office Culture and Employee Behavior in Work Places - Ugwuzor, Miebi (International Journal of Management Excellence (ISSN: 2292-1648), 2016)
Abstract The examination of the behavioural responses of the reciprocal first name exchange as a policy in firms in Nigeria was the main objective of this research. It was also the intent of this empirical work to highlight the challenges and issues of the transferability and applicability of contemporary work culture within the context of the Nigerian cultural environment. For this study, the cross sectional survey design was adopted and the questionnaire method of data collection was used .A non parametric Bivariate Correlation was employed for the purpose of data analysis. The findings revealed that the lower the level of comfort employees felt with the reciprocal use of first names as a policy in workplaces the more dysfunctional their behaviours. It was recommended among other things that corporate policies, practices and strategies must take cognizance of local national cultural specifics.